2018
DOI: 10.5009/gnl17177
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Standard Triple Therapy Plus Probiotics or Concomitant Therapy for Helicobacter pylori Infection

Abstract: Background/AimsThe efficacy of standard triple therapy (STT) in treating Helicobacter pylori infection has decreased. Many investigators have attempted to increase the eradication rate. We investigated the outcomes of concomitant therapy (CT) and STT combined with probiotics (STP) as a first-line treatment for H. pylori infection.MethodsWe reviewed the medical records of 361 patients who received either STP (n=286) or CT (n=75). The STP group received STT combined with a probiotic preparation for 1 week. The C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
(39 reference statements)
0
11
1
Order By: Relevance
“…As the effective treatment duration increases, there is a concern regarding antimicrobial side effects. In one recent study, the addition of a probiotic was shown to reduce the frequency of adverse events from 28.2% in the nonprobiotic group to 12.2% …”
Section: Probioticsmentioning
confidence: 98%
See 1 more Smart Citation
“…As the effective treatment duration increases, there is a concern regarding antimicrobial side effects. In one recent study, the addition of a probiotic was shown to reduce the frequency of adverse events from 28.2% in the nonprobiotic group to 12.2% …”
Section: Probioticsmentioning
confidence: 98%
“…In one recent study, the addition of a probiotic was shown to reduce the frequency of adverse events from 28.2% in the nonprobiotic group to 12.2%. 65 A meta-analysis reported that the addition of a probiotic to bismuth-based quadruple therapy increases the eradication rate by approximately 10%. 14 A systematic review assessed the efficacy of probiotics as monotherapy.…”
Section: Prob Iotic Smentioning
confidence: 99%
“…The gram-negative, flagellated bacteria Helicobacter pylori is typically found on the luminal surface of the stomach epithelium. Because of severe side effects and changes in natural flora, the efficacy of standard triple therapy (STT) in treating Helicobacter pylori infection has declined [ 64 ]. Probiotics improve immune-regulation functions, which operate as an antidote to Helicobacter pylori infection, and hence inhibit Helicobacter pylori infection.…”
Section: Therapeutic Use Of Probioticsmentioning
confidence: 99%
“…14 of this book. For example, one recent study reported that the addition of a probiotic reduced the frequency of adverse events from 28.2% to 12.2% (Jung et al 2018). Oh and co-workers (2016) analyzed the microbiome of patients receiving probiotics compared to those receiving antimicrobial eradication therapy alone and found that although the microbiota were similar, as assessed by metagenomes sequencing, there was a greater proportional shift in functional gene families in those receiving antibiotics compared to those receiving the probiotic (Medilac-S ® ; Streptococcus faecium 9 × 10 8 and Bacillus subtilis 1 × 10 8 ).…”
Section: History Of H Pylori Therapiesmentioning
confidence: 99%